Republic of Moldova : Financial Sector Assessment Program-Bank Crisis Resolution-Stress Testing. (IMF Staff Country Reports; Country Report, 2016)
This note discusses the stress tests that were carried out on Moldova's banking system as part of the 2014 Financial Sector Assessment Program (FSAP) Update. The objective of this exercise was to assess the resilience of the banking system to major sources of risk. The stress tests were conducted in collaboration with the National Bank of Moldova (NBM), and complement other approaches, such as the analysis of financial indicators and the assessment of the quality of supervision. The stress tests focused on the banking system and covered all 14 banks operating in the country. Top-down solvency stress tests were conducted jointly by the FSAP team and staff from NBM, using supervisory data. These stress tests were complemented by bottom-up stress tests, conducted by individual banks using their own internal models, but applied to the macroeconomic scenarios provided by the FSAP team. In addition, liquidity stress tests, together with complementary sensitivity analysis were also carried out on all banks in the system.